Late Holocene initiation of a deep rock slope failure in an alpine valley revealed by 10Be surface exposure dating (Chamonix, France). (10th April 2023) - Courtial-Manent, L.; Mugnier, J.-L.; Zerathe, S.; Carcaillet, J.; Vassallo, R.; Ravanel, L.; Tavernier, L.; Buoncristiani, J.-F.
Abstract: We studied a newly identified, multiple-kilometer-long rock slope failure in the Aiguilles Rouges massif (Chamonix valley, France). Owing to a high-resolution light detection and ranging (LiDAR) digital elevation model (DEM) and field work, we mapped morphostructures, including scarps, open fractures, and counterscarps. In some places, vertical offsets can reach tens of meters and crevasses can be meters wide. The evidence of gravitational activity (boulder displacements from analyses of archival satellite images) and the sharpness of the scarp outcrops together suggest very recent movements. These observations agree with ground displacement rates of a few millimeters per year estimated by interferometric synthetic aperture radar (InSAR) time series between 2014 and 2018. We sampled two vertical profiles along the top scarps to define the chronology of the slope failure using beryllium-10 ( 10 Be) surface exposure dating. Glacially polished surfaces cut by these gravitational scarps were also sampled to determine glacial retreat timing as well as to constrain the pre-exposure 10 Be inheritance. In total, 11 samples were studied. Our results highlight a significant time lag (approximately 15 ka) between the first evidence of nonglacial activity and the initiation of the slope failure that happened 1.3–2.5 ka ago, depending on the inheritance schemes. This suggests that the delayed opening of the crevasse is only one stage of a process that began when the valley was deepened and the glacial debuttressing is not the unique driving factor. This process of progressive failure of an excessively steep slope may continue, and the evolution of this slope failure may constitute a hazard for the upper part of the Chamonix valley.